# How do you solve 3x + y = -26 and 2x - y = -19?

##### 1 Answer

#### Answer:

#### Explanation:

Using the method of simultaneous equations, you take the first equation and write

#y=-3x-26#

Then you substitute this into the second equation, ie. wherever you see a

#2x-(-3x-26)=-19#

This then leaves an equation with only one unknown,

#5x+26=-19 #

Therefore

Then substitute back to get the value or

#-3 * (-9) -26 = 1#

An alternative method would be to use linear matrix algebra, in which a separate 3 methods exist :

- Gauss-Jordan elimination
- Inverse matrix method
- Kramer's Rule

Please let me know if you require me to resolve the problem using any of these 3 methods and I will do so for you, otherwise the simultaneous equation method shown above should suffice or a